Parity modifies the effects of fluoxetine and corticosterone on behavior, stress reactivity, and hippocampal neurogenesis. (June 2016) - Workman, Joanna L.; Gobinath, Aarthi R.; Kitay, Nicole F.; Chow, Carmen; Brummelte, Susanne; Galea, Liisa A.M.
Abstract: The postpartum confers considerable risk for developing depression. Depressed patients have elevated cortisol concentrations and impaired hypothalamic-pituitary-adrenal (HPA) axis negative feedback. Chronic stress or corticosterone (CORT) induces a depressive-like phenotype in rodents, including during the postpartum. The present study examined whether nulliparous and postpartum rats were differentially vulnerable to chronic high CORT and whether fluoxetine (FLX) would differentially alter the brain, behavior, and neuroendocrine function depending on reproductive experience. Nulliparous and postpartum female Sprague–Dawley rats were divided into 4 groups that received 21 d of injections of CORT or oil plus FLX or saline. CORT reduced maternal behaviors whereas FLX reversed CORT-induced decreases in maternal care. CORT increased immobility in the forced swim test (FST), but FLX did not significantly alter immobility in either nulliparous or postpartum rats. Dams spent less time immobile and had lower CORT concentrations after the FST compared with nulliparae, indicating that aspects of the postpartum period may provide resilience against a depressive-like phenotype. Both CORT and parity reduced neurogenesis (doublecortin expression) in the dentate gyrus. FLX-treated rats had lower CORT concentrations following the FST and more immature neurons, but only in the nulliparous, and not postpartum, groups. These data suggest that the postpartum may inherently protect against some deleterious effects of high CORT but also confer resistance to the neurogenic and endocrine effects of FLX. Our findings are important for understanding how females in different reproductive states respond to glucocorticoids and antidepressants. Highlights: Parity, but not fluoxetine, reduced immobility in the forced swim test. Fluoxetine attenuated stress-induced corticosterone in nulliparae only. Fluoxetine reversed maternal care deficits with postpartum corticosterone. Fluoxetine increased neurogenesis in the ventral dentate in nulliparae only. Stress-induced increase in corticosterone was reduced in postpartum.